Identification of major and minor allergens of Black Tiger Prawn (Penaeus monodon) and King Prawn (Penaeus latisulcatus) - Sahabudin Syuhaidah, Misnan Rosmilah, Mohammad Yadzir Zailatul Hani, Mohamad Jamaludin, (N/A, 2011)
Identification of major and minor allergens of Black Tiger Prawn (Penaeus monodon) and King Prawn (Penaeus latisulcatus) by Sahabudin Syuhaidah, Misnan Rosmilah, Mohammad Yadzir Zailatul Hani, Mohamad Jamaludin,